Studi Implementasi Marpol Annex I pada Kapal yang Masuk Areal Pelabuhan Sukarno Hatta Makassar - Abu Bakar; Irwan; Adnan; M. Rusdi; Sarifuddin (Politeknik Pelayaran Barombong, 2026)
Pollution of the environment, especially the marine environment, can cause death and damage to living creatures in the sea, such as fish, coral reefs and other marine resources. This research describes the implementation of MARPOL 73/78 Annex I and the implementation of MARPOL Annex I is analyzed using qualitative and quantitative methods for ships entering the Makassar port area. The observation approach is carried out on the ship and in the marine environment of the ship which is anchored and berthed. Interviews were conducted directly with the crew using a questionnaire form following MARPOL Annex I requirements. For the quantitative method, the weight in each item of MARPOL Annex I requirements is determined based on the score for each item divided by the overall item score (100%). From the results obtained from a sample of 15 ships and 30 Engineering Officers who answered questions, several items of MARPOL Annex I requirements for all ships based on observations and interviews did not follow/meet the requirements in elements and sub-elements, such as in element 3,37% of the ppm alarm separation equipment (OWS) did not function and 63% did. In element 4 related to the disposal of waste oil in special areas, 24% said yes and 76% said no. In element 5, sub-element 3,70% of ships recorded the discharge of tank cleaning water, in sub-element 4, only 15% of ships recorded the discharge of oil residue in the Oil Record Book, while 85% did not record it in the Oil Record Book. In sub-element 5, only 45% of ships recorded the discharge of oil residue in the Oil Record Book while 55% did not record it and in sub-element 9, only 35% of ships recorded damage to OWS machine equipment in the Oil Record Book. Even though the implementation of MARPOL Annex I appears to have not been successful enough to meet the standards in elements 3, 4, 5, elements 1, 2, 6 and 7 of the data processing results have met the standards according to the required provisions. To minimize the occurrence of oil pollution from ships in the Makassar port area, the development plans to be achieved must still be implemented in full in accordance with regulatory standards. Based on the results obtained, training (drill) related to plans for preventing and handling emergency waste pollution from ships continues to be carried out in accordance with the provisions and all activities carried out are recorded, and the company continues to improve the capabilities and skills of human resources (HR) who work on its ships so that the implementation of MARPOL Annex I in the Port Area can continue to be maximized.